Análisis de la diversidad genética de la población de Toros Jersey y Brown Swiss importados al Ecuador entre los años 2000-2021. - Guamialama Mayorga, Adriana Vanessa (2022)
Genetic diversity is important for the survival of species, favoring evolutionary processes. The research aimed to evaluate the genetic diversity of the population of Jersey and Brown Swiss bulls imported to Ecuador between the years 2000-2021 through their genealogical information for which an analysis of consanguinity coefficient was carried out, the genetic relationships between bulls imported and currently marketed in Ecuador. From digital and physical catalogs of the bovine semen marketing companies, 67 Jersey bulls and 58 available Brown Swiss bulls were determined, imported between 2000-2021. For the analysis of the flow and genetic relationships, information corresponding to name, international code, country, date of birth of the imported bull and its paternal and maternal ancestors, queries in the databases of the countries of origin of the ancestors, in 4 generations or more, were used. The value of the percentile, consanguinity by pedigree and genomics was evaluated. The statistical analysis was processed in INFOSTAT. The coefficient of consanguinity and the average kinship with the ENDOG v4.8 program. Jersey genetics from the United States and Canada are responsible for 94% and 4% respectively of gene flow to Ecuador, unlike Brown Swiss genetics from the United States 63% and Switzerland 11% is responsible for gene flow to Ecuador. The average age of Jersey bulls evaluated was 12.63 years and Brown Swiss bulls was 7.99 years. Regarding the consanguinity there is a percentage index 7.75% of the Jersey race and 1.12% of the Brown Swiss breed.